An exploration of the experiences and self-generated strategies used when navigating everyday life with Long Covid - Fiona J. Leggat; Celayne Heaton-Shrestha; Jessica Fish; Aloysius Niroshan Siriwardena; Anne Domeney; Carol Rowe; Ian Patel; Judith Parsons; John Blair; Fiona Jones (BMC, 2024)
Abstract Background Around one in ten people who contract Covid-19 report ongoing symptoms or 'Long Covid'. Without any known interventions to cure the condition, forms of self-management are routinely prescribed by healthcare professionals and described by people with the condition. However, there is limited research exploring what strategies are used to navigate everyday life with Long Covid, and experiences that initiate development of these strategies. Our study aimed to explore the range and influence of self-generated strategies used by people with Long Covid to navigate everyday life within the context of their own condition. Methods Forming part of the Long Covid Personalised Self-managemenT support co-design and EvaluatioN (LISTEN) project, we conducted a qualitative study using narrative interviews with adults who were not hospitalised with Covid-19. Participants aged over 18 years, who self-identified with Long Covid, were recruited from England and Wales. Data were analysed with patient contributors using a reflexive thematic analysis. Results Eighteen participants (mean age = 44 years, SD = 13 years) took part in interviews held between December 2021 and February 2022. Themes were constructed which depicted 1) the landscape behind the Long Covid experience and 2) the everyday experience of participants' Long Covid. The everyday experience comprised a combination of physical, emotional, and social factors, forming three sub-themes: centrality of physical symptoms, navigating 'experts' and the 'true colour' of personal communities, and a rollercoaster of psychological ambiguity). The third theme, personal strategies to manage everyday life was constructed from participants' unique presentations and self-generated solutions to manage everyday life. This comprised five sub-themes: seeking reassurance and knowledge, developing greater self-awareness through monitoring, trial and error of 'safe' ideas, building in pleasure and comfort, and prioritising 'me'. Conclusions Among this sample of adults with Long Covid, their experiences highlighted the unpredictable nature of the condition but also the use of creative and wide ranging self-generated strategies. The results offer people with Long Covid, and healthcare professionals supporting them, an overview of the collective evidence relating to individuals' self-management which can enable ways to live 'better' and regain some sense of identity whilst facing the impact of a debilitating, episodic condition. Trial registration LISTEN ISRCTN36407216.